(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of students from the University of Medicine and Pharmacy at Ho Chi Minh city and the University of Economics at Ho Chi Minh city with adequate knowledge and appropriate practices regarding the use of Paracetamol containing medications, and to assess the associations between knowledge and practice with gender, university, year of study. Methods: A cross-sectional study was conducted on 317 students at the University of Medicine and Pharmacy at Ho Chi Minh city and University of Economics at Ho Chi Minh city from August 2024 to June 2025. Results: Among the 317 participating students, 14.2% demonstrated good knowledge regarding the use of Paracetamol containing medications, and 87.7% reported using these medications at appropriate dosages. Knowledge was significantly associated with university and year of study, but not with practice or gender. No significant associations were found between practice and gender or university; however, practice was associated with year of study. Conclusion: The proportion of students with good knowledge regarding the use of Paracetamol containing medications at both University of Medicine and Pharmacy at Ho Chi Minh city and University of Economics Ho Chi Minh city remains low; however, the rate of correct dosage practice is relatively high. Interventions should be implemented to improve students’ knowledge and minimize the risk of Paracetamol overdose, particularly considering the observed associations between practice and both university and year of study.